Banana regime of the European Union, the Caribbean, and Latin America. - SUTTON, Paul (1997)
Identifies the competing interests and parties concerned with the issue of the banana trade in Europe, the Caribbean, and in Latin America. Discusses the various reactions to the new banana regime which went into effect in July 1993.